Football: spectacularly insignificant or unspectacularly significant?. (7th June 2017) - Stone, Chris
Abstract : Football supporters are often projected as being obsessed, emotionally saturated and intensely involved with their club. This may be true for some, but much of the time, the consumption of football is mundanely incorporated with other routine behaviours and actions. Drawing on previous research on football and everyday life, this paper explores how it is both significant and insignificant through the relationship between spectacular and unspectacular consumption. The 'everyday' is used both descriptively and conceptually. The former is illustrated through examples of the ordinary ways in which football becomes entwined with other elements of everyday life. The latter, rooted in the works of everyday life theorists, provides the philosophical tools for contextualizing the meaning of the 'everyday'. This is then put into perspective with contemporary understandings of living in a fragmented and fluid world which raise further questions about the ordinariness of football culture as part of people's everyday lives.